: Korean Politics vs. Taekwon-Do in 1966-2002 : The Organisational History of The International Taekwon-Do Federation in the Context of Korean Political Division, and How to Protect Your Institution Against Political Appropriation - Hanhikangas, Helena (My University, 2023)
This study brings together East Asian Studies and History Research in the context of Sport and Martial Art History of Taekwon-Do, more precisely the International Taekwon-Do Federation (ITF). It explores the organizational history of the ITF and aims to provide new sources and point of views for the present research field, which has been dominated by Taekwondo Studies linked with the South Korean WT Taekwondo, the sport organization also known as the Olympic Taekwondo. The ITF splintered in three identically named ITF groups in 2002. In the light of this study, North Korea was behind the splintering. It had attempted since 1980, when Taekwon-Do was introduced to North Korea by the ITF and the ITF leader General Choi Hong Hi, to get the ITF fully under their control. However, only after the death of the lifelong leader and president, Choi, did North Korea gain a fraction of it under their control. But the core of the ITF remained intact, aiming to protect its status as a constitutional, legal and nongovernmental sport, and martial art institution. The third ITF group, led by Master Choi Jung Hwa, the son of Gen. Choi, seems to have fallen victim to North Korean hybrid interference strategies, which enhanced the splintering of the ITF. With this study I explore the political reasons behind this splintering, and the political co-opting of an international sport and martial art institution. This study will demonstrate that members of sport organisations, although private citizens, can protect their organisations even from the harshest state-level political co-opting when collaborating with each other actively, and that the structures of these sport organisations have the ability to facilitate such task, especially if they are well taken care of.
Keywords: Taekwon-Do, Taekwondo, International Taekwon-Do Federation, ITF, Choi Hong Hi, Cold War, Hybrid Interference, Red Scare, Front Office, North Korea, South Korea